Retention Strategy And Its Impact On Employees’ Job Performance. A Case Study Of A Small And Medium-Sized Enterprise(SME) (Sains Humanika, 2021)
The objective of this paper is to examine the impact of retention strategy on employee’s job performance This study was - conducted at Linaco Manufacturing Sdn Bhd, a Malaysian small and medium-sized enterprise (SME). This research examined the factors affecting the job performance of employees of this company. 85 employees from the respective production units of Linaco voluntarily participated in the survey using questionnaire. The statistical application used are the descriptive analysis, Pearson-Moment correlation, and multiple regression. Cronbach alpha statistic was used to analyze the reliability of the instrument used in this study. Resulted from the analyzed data, all hypotheses are accepted. From the employees’ perception survey, retention strategy has contributed to  employees’ job performance. The finding  indicated that there is relationship between retention strategy and employees’ job performance. The study recommends that the management of Linaco Manufacturing (M) Sdn Bhd. take into account the various aspects of the impact  retention strategy has on employees in order to improve the employee’s job performance. The recommendations may be helpful to improve the various retention strategy of Linaco Manufacturing(M) Sdn Bhd. and other organisations that may share the same characteristics as Linaco.
Keywords: Retention strategy; employee job performance; human resource management; SME